Rudolf Perco 1884-1942 Von der Architektur des Roten Wien zur NS-Megalomanie - Prokop, Ursula (2001)
Rudolf Perco, one of the most promising pupils in Otto Wagner's late period as teacher received numerous honourable mentionings and awards while still a student (1906 - 10) and so may well have expected a brilliant career. However, after World War I, he could realize only very few projects and his name became forgotten. It was only in the scope of the large scale public housing plan of Red Vienna in the 1920es, that he was given opportunities to materialize his Wagner based ideas, and to build several communal housings, of which the Engels Platz - Hof is the largest and most important. Besides, he submitted entries to a vast number of competitions, for which he designed projects, whose very personal features bring him close to Josef Plečnik.